Efficacy of Azacitidine in autoimmune and inflammatory disorders associated with myelodysplastic syndromes and chronic myelomonocytic leukemia. (April 2016) - Fraison, Jean-Baptiste; Mekinian, Arsène; Grignano, Eric; Kahn, Jean-Emmanuel; Arlet, Jean-Benoit; Decaux, Olivier; Denis, Guillaume; Buchdahl, Anne-Laure; Omouri, Mohamed; Maigne, Gwenola; Aouba, Achille; Leon, Nathalie; et al.
Highlights: AID associated to MDS/CMML is difficult to manage. Azacitidine can improve the control of AID associated with MDS/CMML. Azacitidine allows to reduce steroid dose in most MDS patients with concurrent AID. Azacitidine can be beneficial on AID, even when inactive on the underlying MDS/CMML. Abstract: This retrospective study describes efficacy of Azacitidine on autoimmune disorders (AID) associated with MDS/CMML in 22 patients. Response of AID to Azacitidine was observed in 19 patients (86%). Reduction or discontinuation of steroids and/or immunosuppressive therapy (IST) was possible in 16 cases (73%). Hematologic response was seen in 55% of the patients. MDS/CMML and AID evolution was concordant in 13 cases (59%): both favorable (n = 11), both unfavorable (n = 2), but AID improved while MDS/CMML worsened (n = 8) and vice versa (n = 1). Azacitidine frequently seems effective in controlling steroid-dependent AID associated with MDS/CMML, but prospective studies are necessary to confirm those findings.